Analysis and Design of Dual Mode Power Split Continuously Variable Transmission - Zhen Wang; Yahui Cui; Baohui Xu; Xiaofeng Xue (Jixie chuandong)
Abstract A system approach is proposed for the analysis and design of dual mode power split continuously variable transmission. The characteristic equations of speed ratio， torque ratio and power split ratio of power split continuously variable transmission based on mechanical point are established. By setting the limit on the speed ratio， torque ratio and power split ratio， the feasible region of mechanical points is obtained. The schematic diagrams of power split continuously variable transmission are given. The feasible region of the basic speed ratio is obtained from the feasible region of the mechanical point. By using 2K-H（NGW） type simple planetary gear set， the feasible structure schemes are obtained. By setting the mode shift conditions， the input split and the compound split are synchronously switched at mechanical point of the lower speed ratio and 3 structural diagrams are obtained. By setting two mechanical points to 0.66 and 1.33， the structural scheme of the dual mode power split continuously variable transmission is obtained. Through mode shift， the structural scheme can effectively reduce power， speed， torque of the continuously variable transmission branch. When the speed ratio range is <alternatives>0.4<τ<1.8 <?fx-imagestate width="19.72733307" height="2.70933342"?> <?fx-imagestate width="19.72733307" height="2.70933342"?> </alternatives>， the system efficiency is higher than 90%.